Theoretical Study of the Spectroscopic Constant and Anharmonic Force Field of $PO^-_2$ (Journal of Atomic and Molecular Sciences, 2015)
The equilibrium structure, spectroscopy constants and anharmonic forcefield of $PO^-_2$ anion have been investigated at MP2, B3LYP, B3P86, B3PW91 methodsemploying three basis sets, 6-311++G(2d,2p), 6-311++G(3df,3pd) and cc-pVQZ, respectively.The computed geometries, rotational constants, vibration-rotation interactionconstants, quartic centrifugal distortion constants, and coriolis coupling constants of $PO^-_2$ are compared with the available experimental or theoretical data. The fundamentalfrequencies, rotational constants of ground state, sextic centrifugal distortion constants,cubic and quartic force constants of $PO^-_2$ are firstly predicted. The calculated resultsshow that the B3P86/6-311++G(3df, 3pd) results are in excellent agreement withexperiment and represent a substantial improvement over the results obtained fromMP2. The other DFTmethods are also advisable choices to study the anharmonic forcefield of $PO^-_2.$ The predicted spectroscopic constants may provide the useful data forthe experiment studies of the corresponding spectroscopic constants of $PO^-_2.$
Keywords: $PO^-_2$ anion; ab initio calculations; spectroscopic constants; anharmonic force field.